Ordinance No. 520, § 2, Vancouver City Council, (1910) (Vancouver, Washington). - (:unkn) unknown (My University, 1910)
Any person or persons who shall draw any species of fire arms or any dagger, dirk or knife or any other deadly or dangerous weapon upon the person of another or shall conceal upon his person any of the above weapons or any dangerous weapon, excepting a peace officer in the discharge of his official duties, within the limits of the City of Vancouver, shall be deemed guilty of a misdemeanor."
Keywords: BRANDISHING; CARRY - CONCEALED